Magnetically Guided Capsule Versus Conventional Gastroscopy for Upper Abdominal Complaints. Issue 2 (February 2015) - Denzer, Ulrike W.; Rösch, Thomas; Hoytat, Bilal; Abdel-Hamid, Mohammed; Hebuterne, Xavier; Vanbiervielt, Geoffroy; Filippi, Jérôme; Ogata, Haruiko; Hosoe, Naoki; Ohtsuka, Kazuo; Ogata, Noriyuki; Ikeda, Keiichi; et al.
<x xml:space="preserve">Abstract</x> Objectives: Upper gastrointestinal endoscopy is mostly performed under sedation and has a low yield of relevant gastric lesions in patients without alarm symptoms. Simpler screening tests such as capsule endoscopy could be helpful, but gastric visualization is insufficient with the current passive capsules. A magnetically guided gastric capsule was prospectively evaluated in patients with routine indications for gastroscopy. Methods: A total of 189 symptomatic patients (105 male; mean age 53 y) from 2 French centers subsequently and blindly underwent capsule and conventional gastroscopy by 9 and 6 examiners, respectively. The final gold standard was unblinded conventional gastroscopy with biopsy under propofol sedation. Main outcome was accuracy (sensitivity/specificity) of capsule gastroscopy for diagnosis of major gastric lesions, defined as those lesions requiring conventional gastroscopy for biopsy or removal. Results: Twenty-three major lesions were found in 21 patients. Capsule accuracy was 90.5% [95% confidence interval (CI), 85.4%-94.3%] with a specificity of 94.1% (95% CI, 89.3%-97.1%) and a sensitivity of 61.9% (95% CI, 38%-82%). Accuracy did not correlate with lesion location, gastric luminal visibility, examiner case volume, or examination time. Of the remaining 168 patients, 94% had minor and mostly multiple lesions; the capsule made a correct diagnosis in 88.1% (95% CI, 82.2%-92.6%), with gastric visibility and lesion location in the proximal stomach having significant influence. All patients preferred capsule gastroscopy. Conclusions: In a prospective and strictly blinded study, magnetically guided capsule gastroscopy was shown to be feasible in clinical practice and was clearly preferred by patients. Improvements in capsule technology may render this technique a future alternative to gastroscopy.